2015
DOI: 10.21031/epod.02072
|View full text |Cite
|
Sign up to set email alerts
|

Madde Tepki Kuramına ait Parametrelerin ve Model Uyumlarının Karşılaştırılması: Bir Monte Carlo Çalışması

Abstract: Bu çalışma, Madde tepki kuramının farklı uygulamalarından elde edilen parametrelerin ve model uyumlarının örneklem büyüklüğü ve test uzunluğu açısından karşılaştırılması isimli doktora tezinden üretilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…Araştırmanın bu bulgusu kategori sayısının artmasına bağlı olarak ölçme geçerliliğinin arttığını ifade eden KTK kapsamında yürütülen bazı araştırmalardan (Lozano, García-Cueto ve Muñiz, 2008;Preston ve Colman, 2000) farklı çıkmıştır. Ayrıca KTK kapsamında yürütülen ve kategori sayısının geçerliği etkilemediğini ifade eden araştırmalara (Erkuş, Sanlı, Bağlı ve Güven, 2000;Maydeu-Olivares ve diğerleri, 2009;Uyumaz ve Çokluk, 2016) (Smits, Timmerman ve Meijer, 2012;Şengül Avşar ve Tavşancıl, 2017;Koğar, 2015).…”
Section: Maddelere Ait Model Veri Uyumu Düzeyleriunclassified
See 3 more Smart Citations
“…Araştırmanın bu bulgusu kategori sayısının artmasına bağlı olarak ölçme geçerliliğinin arttığını ifade eden KTK kapsamında yürütülen bazı araştırmalardan (Lozano, García-Cueto ve Muñiz, 2008;Preston ve Colman, 2000) farklı çıkmıştır. Ayrıca KTK kapsamında yürütülen ve kategori sayısının geçerliği etkilemediğini ifade eden araştırmalara (Erkuş, Sanlı, Bağlı ve Güven, 2000;Maydeu-Olivares ve diğerleri, 2009;Uyumaz ve Çokluk, 2016) (Smits, Timmerman ve Meijer, 2012;Şengül Avşar ve Tavşancıl, 2017;Koğar, 2015).…”
Section: Maddelere Ait Model Veri Uyumu Düzeyleriunclassified
“…It is observed in the literature review that several studies in which the psychometric properties of the scales are examined according to the NIRT models are carried out in Turkey and abroad (Galindo Garre et al, 2014;Sachs, Law, and Chan, 2003;Koğar, 2015;Şengül, Avşar, and Tavşancıl, 2017;Young, Blodgett and Reardon, 2003). Especially in the studies on the polytomous items, researches are carried out on both simulated and real data sets according to various factors such as sample size, the number of items and distribution of sample.…”
Section: Extended Abstractmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Köse stated that, based on RMSD values, the increase in the number of items in ability parameter estimation caused less defective results. Koğar (2015) carried out a Monte Carlo study using unidimensional, unidimensional non-parametric and multidimensional IRT models and analyzed the effect of different sample sizes (100, 500, 1000, and 5000), different test lengths (5, 15, and 25) and different inter-dimensional correlation values (0,00, 0,25, and 0,50) on item parameter estimation and model fit. The results suggested that, in unidimensional and multidimensional models, in order for the item parameter estimation to be more accurate, the sample size and test length should be greater.…”
Section: Introductionmentioning
confidence: 99%